The Trial of Jesus Christ - Legal Reflections on Freedom of Thought, Conscience and Religion - Ion, Gabriel Florinel; Ionescu Dumitrache, Ana Alina (Acta Universitatis Danubius. Juridica, 2025)
The trial of Jesus Christ represents one of the most emblematic and historically debated events in the history of Western civilization. Beyond its religious significance, the trial provides a profound opportunity for legal reflection, especially when analyzed through the lens of human rights. This article examines the legal context, procedures, and implications of the trial of Jesus, aiming to identify violations of fundamental rights and draw parallels between ancient legal systems and modern standards of justice. The first part of the study explores the dual legal context of the time—the Jewish religious law and the Roman civil law—highlighting the systemic tensions between these two forms of authority. It analyzes the characteristics of each legal framework and how their interaction shaped the proceedings against Jesus. Special attention is given to the clash between religious orthodoxy and political expediency, which resulted in a trial that departed from both procedural fairness and ethical principles. The second part investigates the trial from a juridical standpoint, assessing whether it respected or violated legal norms of its time. It evaluates the actions of the Sanhedrin and the Roman governor Pontius Pilate, underlining their legal limitations and political motivations. The third part extrapolates the legal lessons for contemporary human rights, focusing on freedom of religion, freedom of expression, and the separation of powers. The trial serves as a case study for examining the dangers of religious influence on civil justice and the enduring relevance of legal safeguards. Finally, the article addresses current legal disputes involving conflicts between religious norms and state laws, providing recommendations for maintaining a balanced, rights-based legal framework in pluralistic societies. This scientific article summarizes the essence of a future bachelor’s thesis.